Afetividade e escola : uma relação em construção - Oliveira, Maristela Fatima dos Santos (2011)
This thesis aims to show the importance to be given to the affective aspect in the teaching and learning. Whereas each person's stage of development, it is understood that each child is different cognitively and affectively. The survey, and the theme, born of the troubles experienced in the school context, through the practices and actions articulated in everyday life. In the first chapter, the subject is the emotion and learning, definitions, concepts and challenges encountered in school, the teacher- student, student-student and affection in the classroom. In the second chapter, it is the affection and teaching practice through studies and research on education practices in different schools: traditional, new school and the technicalities, the educator's role as mediator and the challenge to establish emotional bonds with their students. The classroom is a space for inclusion of people with different values and ways of life, symbolizing the cultural diversity, is important for the teacher know how to express affection by students, through their teaching, since, teaching is work and relate to humans, which suggests a teacher carrying emotional balance, which guarantees peaceful coexistence with the diversity in living classroom. Every action must be related to educational goals proposed by the teacher, the student and school, this relationship will depend on the success or failure of the teaching and learning, which can generate truancy, or in other words, exclusion. The third chapter, the subject addressed emphasizes the affective school, the school that everyone dreams. One school whose environment provides a cheerful space, space of knowledge, of solidarity and affection. It's in the school space, in which the coexistence, cooperation and exchange of feelings makes us more human. This is the school working together in partnerships and dialogue. A school committed to education, with a shared education, solidary, in which there is no room for exclusion.